(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
In the past two decades, managing and raising the general level of environmental awareness on all levels of society has become one of the main social goals that has reached a level of social and political consensus unseen ever before. Considering that only things that can be measured can actually be managed, the measuring of environmental awareness based on scientific criteria is becoming increasingly interesting to scientists working in different disciplines. As these disciplines developed, numerous laws were discovered, models were developed and limitations which should be taken into consideration were defined. However, there is a lack of literary sources that could offer a review of scientific knowledge acquired so far and provide a certain “check list” for researchers. The purpose of the present research is to determine and discuss the key issues that should be considered while creating measurement instruments, conducting analysis of research results and interpreting them. Based on the analysis of relevant theoretical cognitions and empirical research results, the paper provides an overview of key issues and categorises them in three groups: issues in measuring different components of attitude, issues concerning the attitude – behaviour gap and issues concerning the influence of social desirability and research sample. By considering all of these issues it is possible to account for and minimize their negative influence and to contribute to the quality, universality and comparability of the obtained results, as well as of the developed models and the defined laws. Keywords: Environmental awareness, measuring, issues, attitude components